Collins Picture Atlas - Evans, Steve (HarperCollins Publishers, 2015)
This picture atlas is designed to take children on an exciting journey around the world. The atlas opens with the continents, then presents a world view of countries before exploring deeper into each country and the exciting places to visit within each. The maps are clear, colourful and perfect for children to explore the world and let their imaginations run riot. Illustrated by Steve Evans. This book is ideal for home or school and finding out more about the world whilst also helping to develop essential reading skills. Clear, colourful, highly informative, illustrated mapping designed for young readers. Arranged by continent for easy reference. Facts about the world we live in are included on each spread.